Managing diversity: challenges and strategies of International Ethnic 91 Restaurant in Malaysia. - Che Ishak, Farah Adibah; Amir Hamzah, Anis Nabilah (Universiti Teknologi Mata, 2024)
Malaysia, known as a "food paradise", offers its residents and tourists a diverse culinary landscape with a wide variety of local and international dishes. However, operating a successful international ethnic restaurant in Malaysia presents unique obstacles that may differ from those in other countries. Cultural adaptation is crucial as they strive to cater to local preferences while maintaining the authenticity of their cuisine. Customer preferences present another hurdle, with Malaysian diners having diverse tastes and expectations. Adapting menus and presentation styles while preserving the essence of the cuisine is complex but necessary. In fact, managing a diverse workforce from different cultural backgrounds adds complexity to operations. Thus, the objectives of this research are to explore the challenges faced by international ethnic restaurant in Malaysia and to identify the strategy in managing these restaurants. This study adopted a qualitative research approach. 13 in-depth interviews were conducted with restaurant owners and managers, allowing for a comprehensive understanding of the challenges they faced. These interviews were guided by a semi-structured interview protocol to ensure consistency and facilitate in-depth exploration of the research topic. Observations were also conducted to complement the interview data, providing additional insights into the operational dynamics of international ethnic restaurants. Data were analyzed thematically where codes, categories and themes were formed. The findings of this research found that the challenges faced by international ethnic restaurants are labor force obstacles, issues with ingredient acquisition, atmosphere hurdles creation and complexities in restaurant management. Moreover, the finding provided effective strategies such as culinary adaptation, maintaining consistency, customer engagement, effective workforce management, crafting ambience and creating a unique value proposition. By exploring and addressing these challenges, the research aimed to contribute to the growth and success of international ethnic